Beyond Telling Tales: A Cyclical-Integrative Storytelling Model for Internalising Islamic Values in Early Childhood Education - Jimi Harianto; Siti Sholeha; Khaqiqotul Istiqomah (Indonesian Journal of Progressive Pedagogy, 2026)
Early childhood Islamic religious value education necessitates Early childhood character formation, which requires developmentally appropriate approaches to internalise moral and religious values effectively. This study aims to identify and analyse strategies for internalising Islamic religious values through storytelling in early childhood education. A descriptive qualitative case study design was employed involving three teachers, five parents, and twenty children as observation subjects, with data collected through passive participatory observation of 12 learning sessions, in-depth interviews, and document analysis. Thematic analysis using an interactive model was conducted to identify recurring pedagogical patterns. The findings reveal four integrated strategies used by teachers: contextual preparation of story materials, interactive and dramatic storytelling delivery, participatory activation through question–and–answer and role-playing activities, and transformative reinforcement by connecting stories with children’s daily experiences. Observational data from 240 behavioural responses show the predominance of active verbal and nonverbal participation among children during storytelling sessions. The study contributes a cyclical-integrative storytelling strategy model and recommends its application in teacher training and curriculum development to strengthen Islamic character education in early childhood learning contexts.